Calculating the dose of cisplatin that is actually utilized in hyperthermic intraperitoneal chemotherapy among ovarian cancer patients - Wu-yun Wang; Miao-fang Wu; Dong-bing Wu; Li-juan Wang; Hui Li; Zhong-qiu Lin; Jing Li (BMC, 2021)
Abstract Background Hyperthermic intraperitoneal chemotherapy (HIPEC) is an important treatment for ovarian cancer. A certain portion of cisplatin exits the body via the perfusate at the end of HIPEC, so full-dose utilization cannot be achieved. Herein, we sought to explore how much cisplatin is actually utilized and its prognostic influence. Methods Cisplatin (70 mg/m2) was given at 43 °C for 90 min. The actually utilized dose (AD) of cisplatin was calculated using the following formula: AD (mg) = total dose (TD) (mg)-losing dose (LD) (mg); LD = volume (ml) of the perfusate (VPretained) that was retained in the HIPEC treatment system at the end of HIPEC * concentration of cisplatin in the perfusate (mg/ml). Result Sixty-two ovarian cancer patients were included. The median TD, median LD and median AD were 95 mg, 20.7 mg and 75.8 mg, respectively. The utility rate of cisplatin (AD/TD ratio) was 79.2%. On simple linear regression analysis, the TD and VPretained were found to significantly predict the AD. Based on these two factors, multiple linear regression analysis was conducted, and a significant regression equation was formulated [F (2, 59) = 71.419, P < 0.0001]: predicted AD (mg) = 30.079 + 0.667 TD (mg) - 0.010 VPretained (ml) (adjusted R 2 = 0.698). In Cox regression analysis, AD was not noted to be associated with progression free survival or overall survival. Conclusion For ovarian cancer patients who receive cisplatin for HIPEC at 43 °C, the AD of cisplatin can be predicted using a regression equation and it has no prognostic impact.